The Analyses of Women Role On Part-Time Workers In Junrejo Batu City - Uci Yuliati, MM (Jurnal Perempuan dan Anak, 2019)
This reseach is carried out in Junrejo Sub-distric. Part-time women workers are the  respondents of this research. This reseach is very important to be done because the women workers dominate informal working sectors. Therefore, it is interesting to learn deeply about their activities profile, access and control profile, beneficial and impact profile  while doing their job. It is also looks at pushing factors which motivate women worker in doing their job, job pattern, interesting job, and how they arrange their time in and out of their home.The number of respondents are 153 part-time women workers. Questionairres are used as an instrument for data collecting. SPSS program is used to analyse cross-tabulation various profiles above. The result of analysis shows that part-time women workers’ activities profile can be classified into some jobs such as farmer helpers, waitres at home, (vendors) sellers of vegetables and cake, Javanesse salad (rujak), and workers in home industries.